Drone photogrammetry: a structural data gathering tool for open pit mining geotechnics - Dey, J.; Roy, S.; Matin, A. (SSIM 2021: Second International Slope Stability in Mining, 2021)
Structural elements, such as folds, faults, shear zones (major structures) and closely spaced structural defects (structural fabric) determine the stability of open pit slopes. As a result, a site-specific structural model is required for reliable slope design, its implementation and management. However, attaining a robust fabric model is often difficult for lack of adequate and reliable data, and therefore, uncertainty is introduced in the resulting pit designs. To overcome data inadequacy and uncertainty, drone flights were used to develop a photogrammetry-based model of an operating limestone pit. The deposit occurs in a structurally complex terrain with varied orientation of strata and joint systems typical of a folded sequence. An automated mission plan was devised with the drone flying at a constant speed in a predefined path, maintaining a constant distance from the pit benches. Images were captured automatically with vertical, inclined, and horizontal camera angles. The high resolution, 3D photogrammetric model was processed by Datamine Sirovision package. Different lithologies, their contacts, and the fabric systems were captured through the process and were used for structural interpretation and modelling. At project scale, the deposit showed signatures of three phases of deformation: 1) a bench to sub-bench-scale isoclinal folding; 2) mine-scale upright, open folding with ~E-W trending axial plane; and 3) mine-scale cross folding with ~N-S trending axial planes. Orientation of bedding planes were largely controlled by the first order second generation folding. Sub-vertical, persistent, axial planes associated with the two major folding episodes (2 and 3) formed the most prominent structural fabric that strikes ~E-W and ~N-S, respectively. In addition, sub-horizontal, small-scale, axial planes associated with the first phase of folding were found locally alongside partially developed joint sets. Structural domains were outlined based on rock mass conditions and structural fabric. Resulting structural model helped to develop a reliable geotechnical model, established opportunities of slope steepening, and finally to develop a slope management program.